Expanding Nursing Faculty Development Through a Fitness Initiative - Crystal Walker; Sally Humphrey; Vicki Chandler (The Ohio State University Libraries, 2022)
Background: Prioritizing fitness in the workplace can aid in promoting a more contemporary view of faculty development. As a result, a workplace fitness initiative was developed in a Southern college of nursing to address the physical activity of faculty and staff during work hours and to promote a more contemporary view of faculty development. Aim: This study examined perceptions of the fitness initiative and explored opportunities for improvement. Methods:  Faculty and staff completed a survey about the fitness initiative including perceptions of workplace fitness, motivation to join, most enjoyable aspects of the fitness initiative, and opportunities for improvement.  Data were analyzed using descriptive statistics, and qualitative responses were coded and analyzed using thematic content analysis. Results: One hundred percent of survey respondents (n = 35) believed in the importance of workplace fitness. Four themes were identified related to the perception of workplace fitness: workplace fitness can increase self-reported movement and productivity and support personal goals. Survey respondents also appreciated the comradery, connection, and team-building that the initiative created. However, time was a barrier to engagement. Conclusion: As nurses are urged to model health-promoting behaviors, a college fitness initiative should be considered for encouraging and normalizing workplace fitness and promoting a more contemporary view of faculty development that focuses on factors outside the traditional faculty role. Our fitness initiative demonstrated that such programs are feasible, well-accepted, promote fitness in physical or virtual workplaces, and help to build connection and comradery among faculty and staff.